Online Consumer Engagement Toward Cross Cultural Products in Japanese Restaurant Franchise Marugame Udon - Ariyanthi, DEWI Rina (CENTRAL ASIA AND THE CAUCASUS, 2022)
Foreign market often comprises unfamiliar challenge due to different culture. The creation of cross-cultural products by foreign company is highly welcomed by the consumers from any local market. Cross-cultural products can give favorable outcomes for the company intent to succeed in foreign market. This paper aim to look at Marugame Udon cross cultural product which localized its Japanese udon noodle with extra spicy flavor common to Indonesian culinary. Marugame Udon utilized online platforms to launch its new spicy menu during the time of movement restriction by Indonesian government due to COVID-19 pandemic. Therefore, this paper aim to observe online consumer engagement toward Japanese cross-cultural product from Marugame Udon by employing the five consumer engagement sub- processes for the development of consumer engagement meaning in online context. The result provides iterate interaction between the consumers and the company which led to favorable outcomes of loyalty, empowerment, connection and trust.